A possibilidade de uma fenomenologia-hermenêutica naturalizada: desenvolvimento linguístico infantil como campo fenomênico - Tronco, Júlia Garcia (2024)
The growing interest in a link between phenomenology and empirical science research brings with it the possibility of developments and refinements in analyses, questions and investigations regarding consciousness and meaningful human experience. The main investigations of this link arise between phenomenology – mainly the husserlian one – with the so-called Cognitive Sciences and range from the basic study of cognitive processes, to studies in language, neuroscience, behavior, action, social cognition, artificial intelligence, attention, among other topics of phenomenology and, mainly, of psychology. These attempts to link phenomenology and empirical sciences, especially the Cognitive Sciences, are attempts to naturalize phenomenology. Based on this, the present thesis aims to approach this link, however, considering the possibility of a naturalization of Martin Heidegger's hermeneutic phenomenology. Therefore, it will be used as a phenomenal field of study the linguistic development in children – from a specific phenomenon: the joint attention. The hypothesis defended in this thesis is that the phenomenon of joint attention is a fundamental element in linguistic development on human infants. To defend this hypothesis, the hermeneutic phenomenological method linked to studies in the areas of cognitive sciences will be used. At the end of the thesis, two questions are expected to be resolved, whether in fact the hypothesis of joint attention is sustained and whether hermeneutic phenomenology is subject to naturalization. The thesis is divided into two parts. The first operates as an introduction and reconstruction of three aspects: first, of the phenomenological method – mainly of husserlian phenomenology. Then, the cognitive sciences and current attempts to naturalize and link it are presented. Then, the hermeneutic phenomenology and the possibilities of naturalization are presented. The second part, on the other hand, falls within of the investigative scope of the general hypothesis of the thesis: use the hermeneutic phenomenological method in line with the cognitive sciences to analyze whether the phenomenon of joint attention is a fundamental part of linguistic development in human early childhood.